Reaction of Metal Ion with Water Soluble Dyes From Red Dragon Fruit Peel (Hylocereus costaricensis (F.A.C Weber) Britton & Rose) - Ichsan, Firman
Red dragon fruit peel has been known to have a high content of dye that can be used as natural dye candidate. However, it was found that the color of the peel of red dragon fruit tends to be unstable by the presence of metal ions. This study aimed to assess the effect of metal ions are ions of copper (II), manganese (II), cobalt (II), nickel (II), cadmium (II), aluminum (III), magnesium (II), calcium (II), iron (II) and lead (II) against the absorbance peak profile red dye from a red dragon fruit peel. Dragon fruit peel is extracted by various solvents such as ethanol, water, glycerol, 1M HCl and 1M NaOH. Furthermore, viewed from the profile spectrum in UV-visible light with the composition of the ethanol-water and glycerol-water (4: 0, 7: 1, 3: 1, 5: 3, 1: 1, 3: 5, 1: 7 and 0: 4). The composition of ethanolwater (1: 1) is reacted with metal ions to see the profile of absorptivity of the reaction products with the ratio of the height, and the shift of peak wavelength. On ethanol, water and glycerol are likely to generate peak absorbance at 530 nm and shows a red rosa and red. The results of the spectra, the composition of the ethanol-water (1: 1) yields the highest absorbance value by 2.41. While the composition of the glycerol-water (7: 1) yields the highest absorbance value of 1.58. There are three metal ions affect the shift in spectral peaks of UV-visible light to the left in the dye samples of the red dragon fruit i.e. copper ions (II) 42 ± 2 nm, ions of lead (II) 41 ± 2 nm and iron (II) 5 ± 2 nm. While shifting the peak absorbance in the right direction there are five ions are ions of cobalt (II) 8 ± 2 nm, ion manganese (II) 6 ± 2 nm, ion cadmium (II) 6 ± 2 nm, ion nickel (II) 4 ± 2 nm and calcium ions (II) 3 ± 2 nm. Of various metals, which raises the intensity of the absorbance of the sample only added magnesium ion (II) by 57 ± 6% and iron (II) 55 ± 2%. Samples were added other metal ions other than magnesium (II) and iron (II), lower the intensity of the absorbance spectrum of UV-visible light, especially samples reacted with ions of lead (II) ions and manganese (II) of 1.111 ± 2%.